Attitude of the Dental Undergraduate Students and Interns towards Dentistry Post COVID-19 - Bhat, Supriya; Gadiyar, Akshatha (Journal of Health and Allied Sciences NU, 2022)
Introduction The period of coronavirus disease 19 (COVID-19) is a significant period from various aspects such as world health and socioeconomic considerations. The majority of the hospitals involved in dental education had previously limited their clinical practices to dental emergencies, but now are geared up for nonemergent conditions. As teaching modalities shifted to online platforms, students have reported to be anxious with regard to accomplishment of required clinical skills, patient care, and forthcoming graduation. Fresh graduates have reported a delay in the drive, which they would have been able to achieve in the initial stages of their profession.Objectives To assess the attitude of the dental undergraduate students and interns toward dentistry post-COVID-19.Results The majority (80.2%) were prepared for the challenges lying ahead before beginning to work on patients. Also, 16% were willing to treat patients, 28% did not want to treat patients, while 44% were willing to handle emergency cases. Next, 67.8% were scared of infecting themselves while administering dental treatment and 78.9% were concerned that there could be more such pandemics. In total, 21.6% of the respondents who wished that they chose an alternate profession whereas 70.5% of participants felt that the scope of dentistry has not diminished. Also, 90.7% were interested to pursue postgraduation, and 86.3% felt that this was a passing phase and things would be normalized soon.Conclusion With second and third waves being rampant, novel coronavirus has become a public health crisis. Because dental services cannot be stopped for a long time, it is essential for dental students to be well trained to limit the spread of the disease. Owing to the present scenario, appropriate donning and doffing of PPE (personal protective equipment) is a pivotal step in direct patient care, and simulation-based training may help ensure that these skills are acquired by them.
Keywords: attitude; COVID-19; dentistry; students